Perception of a Peer Health Coaching Intervention Among College Students: Client Experience - Benes, Sarah; Oh, Seungbin; Peacock, Jessica; Yan, Zi (American Journal of Health Education, 2023)
Keywords: dept.hms; peer-reviewed

The impact of an 8-week wellness peer coaching program on physical activity among college students: 1338 - Peacock, Jessica; Yan, Zi; Bowling, April; Benes, Sarah (Medicine & Science in Sports & Exercise, 2023)
An abstract is unavailable.
Keywords: dept.hms; peer-reviewed

An 8-week peer health coaching intervention among college students: a pilot randomized study - Yan, Zi; Peacock, Jessica; Cohen, Juliana F. W.; Kurdziel, Laura; Benes, Sarah; Oh, Seungbin; Bowling, April (Nutrients, 2023)
This study explored the effects of an 8-week peer coaching program on physical activity (PA), diet, sleep, social isolation, and mental health among college students in the United States. A total of 52 college students were recruited and randomized to the coaching (n = 28) or the control group (n = 24). The coaching group met with a trained peer health coach once a week for 8 weeks focusing on self-selected wellness domains. Coaching techniques included reflective listening, motivational interviews, and goal setting. The control group received a wellness handbook. PA, self-efficacy for eating healthy foods, quality of sleep, social isolation, positive affect and well-being, anxiety, and cognitive function were measured. No interaction effects between time and group were significant for the overall intervention group (all p > 0.05), while the main effects of group difference on moderate PA and total PA were significant (p < 0.05). Goal-specific analysis showed that, compared to the control group, those who had a PA goal significantly increased vigorous PA Metabolic Equivalent of Task (METs) (p < 0.05). The vigorous METs for the PA goal group increased from 1013.33 (SD = 1055.12) to 1578.67 (SD = 1354.09); the control group decreased from 1012.94 (SD = 1322.943) to 682.11 (SD = 754.89); having a stress goal significantly predicted a higher post-coaching positive affect and well-being, controlling the pre-score and other demographic factors: B = 0.37 and p < 0.05. Peer coaching showed a promising effect on improving PA and positive affect and well-being among college students.
Keywords: dept.hms; diet; mental health; peer-reviewed; physical activity; positive affect; sleep; stress